Loco-regionally advance breast cancer: evaluation of management of breast cancer with special reference to multimodal approach - Panda, Anshuman; Das, Subrata Kumar; Gupta, Tapas Ranjan; Kesari, Gouri Shankar; Sen, Sukanta (International Journal of Research in Medical Sciences, 2016)
Background: Breast cancer is one of the most common human neoplasms, accounting for approximately one-quarter of all cancers in females worldwide and 27% of cancers in developed countries with a western lifestyle. The aims of this study were to evaluate the management of loco-regionally advanced carcinoma of breast with special reference to multimodal approach. Methods: The study was conducted on patients with loco-regionally advanced carcinoma of breast, reporting for treatment in a large multi-specialty teaching institute. All patients of stage IIIB were initially treated with neo-adjuvant (induction) chemotherapy (3 cycles), except 4 patients in the study group offered surgery as initial treatment because of small tumor size with limited peu’d orange change in the skin. After this treatment all patients were reassessed with a thorough clinical examination and restaging work upto detect the response of the chemotherapy. All patients who achieved objective response (complete + partial) were offered surgery, followed by CT and RT. Results: About 60% of the patients were in stage IIIB and 32% in stage IIIA. Majority of the tumors were in T4 category (64%). In 28% cases ipsilateral fixed lymph nodes were found. Histopathological examination revealed 76% (38) patients with infiltrating duct carcinoma, 4 patients (8%) had comedo carcinoma, 2 patients (4%) had lobular carcinoma, 2 patients (4%) had medullary carcinoma and 4 patients (8%) had mucinous carcinoma. Both nonresponsive (NR) and disease progression (DP) patients were in stage III B group. About 76.9% patients of stage IIIB (20) achieved partial response. Only 1 patient (33.3%) developed local recurrence after 10 months of completion of treatment. Median disease free survival (DFS) period of this group is 30.2 months. Recurrence rate is stage IIIA patients was 27.7% and in stage IIIB 37.5%. Maximum numbers of disease free patients were found in T3N1 group (85.7%). Patient with N2 and T4 disease chances of recurrence was more than N1 and T3 lesions. Conclusions: Patients with LBAC who are able to complete treatment with chemotherapy, mastectomy, and postmastectomy radiation have a high probability of locoregional control. Neo-adjuvant chemotherapy can make inoperable locally advanced breast cancer operable and with the use of neo-adjuvant CT, breast conservation surgery is possible even in locally advanced breast cancer. Use of post-operative CT and RT can increase the disease free survival period. Use of multimodal treatment in the form of CT, surgery and radiotherapy can increase the disease free survival period in locally advanced breast cancer. The advent of successful multimodal regimens incorporating systemic treatment (chemotherapy or chemohormonal therapy) as well as local therapy (surgery and radiation) has significantly improved disease-free and overall survival as well as local-regional control. Longer follow-up of these conservatively treated patients will be needed, however, to determine whether local-regional control is preserved.